Analisis Penerimaan Bea Balik Nama Kendaraan Bermotor terhadap Penerimaan Pajak Daerah Provinsi DKI Jakarta - Fitri Rahmiyatun; Eka Dyah Setyaningsih; Nurul Hidayah (MONETER - JURNAL AKUNTANSI DAN KEUANGAN, 2020)
Abstract - Motor vehicles in Indonesia, especially Jakarta, are experiencing an increase every year. This is supported because of the convenience provided by dealers in the purchase of motor vehicles which results in the transfer of ownership of a motorized vehicle and triggers the imposition of transfer fees. Transfer of Motor Vehicle Title Fee is the surrender of a motorized vehicle because of the agreement of two parties or one party to a sale or inheritance. The data collection method uses the method of observation, interviews, and documentation studies with the method of analysis in the form of secondary quantitative methods. Based on the data that is processed that the Transfer of Motor Vehicle Title Fee as a variable X and the Regional Tax Revenue of the Province of DKI Jakarta as a variable Y there is a strong significant relationship of 0.615. There is a significant influence between Revenue Transfer Fees for Motorized Vehicles Against Regional Taxes of DKI Jakarta Province by 38% and 62% due to other factors, as well as the simple linear regression equation between Revenue Transfer Fees for Motorized Vehicles to Regional Taxes of DKI Jakarta Province, namely Y = 20,939 + 0.285 X Keywords: Acceptance of Transfer Fees for Motorized Vehicles